The clinical implications of platelet-rich fibrin on periodontal regeneration: A systematic review - Marwa Madi; Ahmed M. Elakel (Saudi Dental Journal)
Objectives: Platelet concentrates have been shown to enhance periodontal regeneration when used as a treatment on their own or in conjunction with bone grafting materials. This systematic review aims to assess the effects of using platelet-rich fibrin (PRF), both alone and in combination with other conventionally used materials, on periodontal regeneration in clinical trials. Materials and methods: A systematic electronic search was performed in the electronic databases MEDLINE (PubMed), Scopus, and Web of Science. Specifically, we searched for English language articles published between 2009 and 2019 that conducted in-human studies and included a summary of the results. Our primary search yielded 220 articles, and of these, 110 were clinical studies. Forty-four articles were then selected for a full reading. Results: Twenty-six randomized control trials (RCTs) met the inclusion criteria and were included in this review. Despite the differences between the reviewed studies, most revealed the ability of PRF to promote periodontal wound healing. The positive effects of PRF were observed in clinical criteria, such as reductions in pocket probing depth (PD) and increases in clinical attachment level (CAL), as well as in the degree of defect bone fill, which was determined either radiographically or by surgical re-entry. Conclusions: Additional studies are needed to compare the clinical outcomes of various PRF application procedures and establish standardized protocols for treating periodontal disease with PRF.